'There Are No Other Options?': Rwandan Gender Norms and Family Planning in Historical Perspective. Issue 2 (April 2020) - Jessee, Erin
Abstract : This article surveys the evolution of Rwandan family planning practices from the nation's mythico-historical origins to the present. Rwanda is typically regarded as a patriarchal society in which Rwandan women have, throughout history, endured limited rights and opportunities. However, oral traditions narrated by twentieth-century Rwandan historians, storytellers and related experts, and interpreted by the scholars and missionaries who lived in Rwanda during the nation's colonial period, suggest that gender norms in Rwanda were more complicated. Shifting practices related to family planning – particularly access to contraception, abortion, vasectomies and related strategies – are but one arena in which this becomes evident, suggesting that women's roles within their families and communities could be more diverse than the historiography's narrow focus on women as wives and mothers currently allows. Drawing upon a range of colonial-era oral traditions and interviews conducted with Rwandans since 2007, I argue that Rwandan women – while under significant social pressure to become wives and mothers throughout the nation's past – did find ways to exert agency within and beyond these roles. I further maintain that understanding historical approaches to family planning in Rwanda is essential for informing present-day policy debates in Rwanda aimed at promoting gender equality, and in particular for ensuring women's rights and access to adequate healthcare are being upheld.